The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1108/ejm-12-2016-0837
|View full text |Cite
|
Sign up to set email alerts
|

Users’ reactions captured by means of an EEG headset on viewing the presentation of sustainable designs using verbal narrative

Abstract: The aim of this paper is to determine whether consumers accept new arguments for choosing a product that adapts to future needs. It is also seeks to investigate whether the design of products and their ensuing advertising and promotion through a sustainable approach by means of verbal narrative ads can generate a more positive emotional response in the future users of the product than with the application of visual narrative ads.To this end, an experiment was conducted consisting in consumers, with and without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 49 publications
(60 reference statements)
0
20
0
Order By: Relevance
“… Price Çakar et al [ 34 ], Marques et al [ 22 ], Çakir et al [ 24 ], Gong et al [ 35 ], Pilelienė and Grigaliūnaitė [ 36 ], Hsu and Chen [ 26 ], Boccia et al [ 37 ], Venkatraman et al [ 38 ], Baldo et al [ 39 ]. Promotion Soria Morillo et al [ 40 ], Yang et al [ 41 ], Cherubino et al [ 42 ], Soria Morillo et al [ 43 ], Vasiljević et al [ 44 ], Yang et al [ 45 ], Pilelienė and Grigaliūnaitė [ 36 ], Daugherty et al [ 46 ], Royo et al [ 47 ], Etzold et al [ 48 ], Chen et al [ 49 ], Casado-Aranda et al [ 50 ], Randolph and Pierquet [ 51 ], Nomura and Mitsukura [ 52 ], Ungureanu et al [ 53 ], Goyal and Singh [ 54 ], Oon et al [ 55 ], Singh et al [ 56 ]. ii.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“… Price Çakar et al [ 34 ], Marques et al [ 22 ], Çakir et al [ 24 ], Gong et al [ 35 ], Pilelienė and Grigaliūnaitė [ 36 ], Hsu and Chen [ 26 ], Boccia et al [ 37 ], Venkatraman et al [ 38 ], Baldo et al [ 39 ]. Promotion Soria Morillo et al [ 40 ], Yang et al [ 41 ], Cherubino et al [ 42 ], Soria Morillo et al [ 43 ], Vasiljević et al [ 44 ], Yang et al [ 45 ], Pilelienė and Grigaliūnaitė [ 36 ], Daugherty et al [ 46 ], Royo et al [ 47 ], Etzold et al [ 48 ], Chen et al [ 49 ], Casado-Aranda et al [ 50 ], Randolph and Pierquet [ 51 ], Nomura and Mitsukura [ 52 ], Ungureanu et al [ 53 ], Goyal and Singh [ 54 ], Oon et al [ 55 ], Singh et al [ 56 ]. ii.…”
Section: Methodsmentioning
confidence: 99%
“… iii. Neural response recording techniques EEG Soria Morillo et al [ 40 ], Yang et al [ 41 ], Chew et al [ 17 ], Cherubino et al [ 42 ], Soria Morillo et al [ 43 ], Yadava et al [ 18 ], Doborjeh et al [ 64 ], Çakar et al [ 34 ], Kaur et al [ 65 ], Baldo et al [ 19 ], Boksem and Smitds [ 57 ], Pozharliev et al [ 20 ], Venkatraman [ 38 ], Touchette and Lee [ 21 ], Yang et al [ 45 ], Pilelienė and Grigaliūnaitė [ 36 ], Shen et al [ 23 ], Daugherty et al [ 46 ], Royo et al [ 47 ], Gong et al [ 35 ], Gordon et al [ 59 ], Hsu and Chen et al [ 26 ], Hoefer et al [ 27 ], Randolph and Pierquet [ 51 ], Nomura and Mitsukura [ 52 ], Bhardwaj et al [ 58 ], Fan and Touyama [ 66 ], Rakshit and Lahiri [ 67 ], Jain et al [ 63 ],Ogino and Mitsukura [ 68 ], Oon et al [ 55 ], Bosshard et al [ 32 ]. fMRI Venkatraman et al [ 38 ], Marques et al [ 22 ], Hubert et al [ 25 ], Hsu and Cheng [ 62 ], Chen et al [ 49 ], Casado-Aranda et al [ 50 ], Wang et al [ 30 ], Wolfe et al [ 31 ], Fehse et al [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Through the ET technology, they found that the youngest participants showed a greater interest for and knowledge of these labels. Eventually, Royo et al [36] conducted an experimental campaign through 40 participants monitored by an electroencephalogram (EEG) headset. They observed emotional and cognitive differences between watching a visual narrative and showing the functionality and use of a pushchair (that provides pro-environmental solutions) and a verbal narrative advertisement that explains the problems and the advantages of using the new product.…”
Section: Studies In the Perception Of Sustainable Products: A Criticamentioning
confidence: 99%